Ritual Mandi Suci Petirtaan Jolotundo Perspektif Coordinated Management Of Meaning (Cmm) - Nuraini; Nurma Yuwita (4, 2025)
Abstract This study examines the sacred bathing ritual at the Jolotundo Bathing Pool as a symbolic communication practice imbued with spiritual and cultural meaning. The analysis is based on the Coordinated Management of Meaning (CMM) theory, which views communication as a multi-layered meaning-making process across six levels: content, speech acts, episodes, relationships, life scripts, and cultural patterns. Thus, each symbol and action in the ritual is understood not simply as a simple activity but as part of a complex structure of meaning. This study employed a qualitative method with a case study approach. Data were obtained through field observations, in-depth interviews with ritual participants, and documentation in the form of related notes and archives. This approach enabled the researcher to capture the meanings contained within the ritual practice in greater depth and context. The results indicate that the sacred bathing ritual at the Jolotundo Bathing Pool is understood not only as a physical purification process but also as a medium of spiritual communication to convey prayers, hopes, and respect for ancestors. Key symbols such as water, flowers, and incense have meanings that are understood both personally and collectively, thus strengthening the spiritual and cultural dimensions of the ritual. Interestingly, the ritual participants come from diverse religious and cultural backgrounds, reflecting the value of inclusivity and the influence of syncretic beliefs. Furthermore, the meaning of the ritual is influenced by individual life experiences, family traditions, and local cultural values ​​passed down through generations. This makes the Jolotundo Bathing Place a dynamic, ever-evolving spiritual space that remains relevant amidst the changes in modern society. Abstrak Penelitian ini membahas ritual mandi suci di Petirtaan Jolotundo sebagai praktik komunikasi simbolik yang sarat makna spiritual dan budaya. Landasan analisis yang digunakan adalah teori Coordinated Management of Meaning (CMM), yang memandang komunikasi sebagai proses penciptaan makna berlapis dalam enam tingkatan, yaitu konten, tindak tutur, episode, hubungan, naskah hidup, dan pola budaya. Dengan demikian, setiap simbol dan tindakan dalam ritual dipahami tidak hanya sebagai aktivitas sederhana, tetapi bagian dari struktur makna yang kompleks. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data diperoleh melalui observasi lapangan, wawancara mendalam dengan pelaku ritual, serta dokumentasi berupa catatan dan arsip terkait. Pendekatan ini memungkinkan peneliti menangkap makna yang terkandung dalam praktik ritual secara lebih mendalam dan kontekstual. Hasil penelitian menunjukkan bahwa ritual mandi suci di Petirtaan Jolotundo tidak hanya dipahami sebagai proses penyucian diri secara fisik, tetapi juga sebagai media komunikasi spiritual untuk menyampaikan doa, harapan, dan penghormatan kepada leluhur. Simbol-simbol utama seperti air, bunga, dan dupa memiliki makna yang dipahami baik secara personal maupun kolektif, sehingga memperkuat dimensi spiritual dan kultural dari ritual tersebut. Menariknya, para pelaku ritual berasal dari latar belakang agama dan budaya yang beragam, mencerminkan nilai inklusivitas dan adanya pengaruh kepercayaan sinkretik. Selain itu, makna ritual dipengaruhi oleh pengalaman hidup individu, tradisi keluarga, serta nilai-nilai budaya lokal yang diwariskan secara turun-temurun. Hal ini menjadikan Petirtaan Jolotundo sebagai ruang spiritual yang dinamis, terus berkembang, dan tetap relevan di tengah perubahan masyarakat modern.